Risk exposure trade-offs in the ontogeny of sexual segregation in Antarctic fur seal pups. (17th March 2020) - Jones, Kayleigh A; Wood, Hannah; Ashburner, Jonathan P; Forcada, Jaume; Ratcliffe, Norman; Votier, Stephen C; Staniland, Iain J
Abstract: Sexual segregation has important ecological implications, but its initial development in early life stages is poorly understood. We investigated the roles of size dimorphism, social behavior, and predation risk on the ontogeny of sexual segregation in Antarctic fur seal, Arctocephalus gazella, pups at South Georgia. Beaches and water provide opportunities for pup social interaction and learning (through play and swimming) but increased risk of injury and death (from other seals, predatory birds, and harsh weather), whereas tussock grass provides shelter from these risks but less developmental opportunities. One hundred pups were sexed and weighed, 50 on the beach and 50 in tussock grass, in January, February, and March annually from 1989 to 2018. Additionally, 19 male and 16 female pups were GPS-tracked during lactation from December 2012. Analysis of pup counts and habitat use of GPS-tracked pups suggested that females had a slightly higher association with tussock grass habitats and males with beach habitats. GPS-tracked pups traveled progressively further at sea as they developed, and males traveled further than females toward the end of lactation. These sex differences may reflect contrasting drivers of pup behavior: males being more risk prone to gain social skills and lean muscle mass and females being more risk averse to improve chances of survival, ultimately driven by their different reproductive roles. We conclude that sex differences in habitat use can develop in a highly polygynous species prior to the onset of major sexual size dimorphism, which hints that these sex differences will increasingly diverge in later life. Abstract : Sexual segregation is common in the animal kingdom, but how it develops is rarely studied. Small sex differences in habitat use occur in Antarctic fur seal pups as males spend more time in riskier habitats than females. Only the "best" males get to reproduce, so they must take risks to gain strength and social skills in preparation for future fights over access to mates. In contrast, females need to prioritize survival and, hence, prefer safer habitats.